Interleukin-6 and RANTES in Takayasu Arteritis: A Guide for Therapeutic Decisions? - Noris, Marina; Daina, Erica; Gamba, Sara; Bonazzola, Samantha; Remuzzi, Giuseppe (Circulation (New York, N.Y.), 1999)
Background —In patients with Takayasu arteritis, circulating lymphocytes are activated, and histological findings indicate that cell-mediated immunity plays an important role in the pathogenetic sequence leading to vascular lesions. Methods and Results —To delineate the profile of inflammatory and chemoattractant cytokines involved in T-cell activation in Takayasu arteritis, we measured by ELISA serum levels of interleukin (IL)-6, IL-1β, and RANTES in 18 patients. Subsequently, we wanted to establish whether any of these molecules could be used as a marker to monitor the clinical course of the disease and to predict disease exacerbations. We found that all patients with Takayasu arteritis studied during an active phase of the disease have increased serum concentration of IL-6 compared with healthy control subjects ( P <0.01). Enhanced IL-6 serum levels paralleled disease activity to the extent that its serum concentrations were comparable to those of control subjects when patients were studied in remission. RANTES concentrations were also higher than normal in the serum of all patients with Takayasu arteritis ( P <0.01) studied during an active phase of the disease. RANTES serum levels tended to normalize in remission, but values remained higher than those of control subjects ( P <0.05). In contrast, serum concentrations of IL-1β were below the detection limit of ELISA in both healthy subjects and all patients with Takayasu arteritis. A positive correlation was found between either IL-6 (ρ=0.705, P <0.01) or RANTES (ρ=0.607, P <0.05) serum level and disease activity. Conclusions —The close correlation of serum IL-6 and RANTES levels with disease activity suggests that these cytokines contribute to vasculitic lesions in Takayasu arteritis and raises the possibility that their monitoring in serum helps clinicians find adequate treatment adjustments in individual patients.